Nitrate, ascorbic acid, mineral and antioxidant activities of Cosmos caudatus in response to organic and mineral-based fertilizer rates - Hassan, Siti Aishah; Mijin, Salumiah; Yusuf, Umi Kalsom; Ding, Phebe; Megat Wahab, Puteri Edaroyati (MDPI, 2012)
The source and quantity of nutrients available to plants can affect the quality of leafy herbs. A study was conducted to compare quality of Cosmos caudatus in response to rates of organic and mineral-based fertilizers. Organic based fertilizer GOBI (8% N:8% P2O5:8% K2O) and inorganic fertilizer (15% N, 15% P2O5, 15% K2O) were evaluated based on N element rates at 0, 30, 60, 90, 120 kg h−1. Application of organic based fertilizer reduced nitrate, improved vitamin C, antioxidant activity as well as nitrogen and calcium nutrients content. Antioxidant activity and chlorophyll content were significantly higher with increased fertilizer application. Fertilization appeared to enhance vitamin C content, however for the maximum ascorbic acid content, regardless of fertilizer sources, plants did not require high amounts of fertilizer.